The impact of health literacy, decision making participation, self-efficacy on patient satisfaction at Bhayangkara Hospital Semarang - Adeline Cornelia Phelps; Mohammad Agung Saryatmo (Universitas Tarumanagara, 2026)
Patient-centered health care underscores the essential roles of health literacy and self-efficacy, encouraging individuals to participate actively in making medical decisions related to their health conditions. This orientation reflects a significant transformation in contemporary healthcare delivery, where patients are no longer positioned as passive recipients of services but are viewed as partners capable of influencing their treatment outcomes. Implementing this approach requires clear communication, accessible and comprehensible health information, and a supportive institutional environment that promotes informed patient engagement. In public healthcare settings such as Bhayangkara Hospital Semarang, patient satisfaction still varies, particularly regarding communication quality, involvement in decision-making, and understanding of medical information. These variations suggest that patients may experience differing levels of support in managing their care. Therefore, this study examines the effects of health literacy, participation in decision-making, and self-efficacy on outpatient satisfaction. A quantitative cross-sectional research design was employed, involving 220 outpatients selected through purposive sampling. Data collection used a Likert-scale questionnaire adapted from the Health Literacy Questionnaire (HLQ), the Patient Activation Measure (PAM-13), the General Self-Efficacy Scale (GSE), and the Patient Satisfaction Questionnaire (PSQ). Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4 to assess construct validity, reliability, and relationships among variables. The findings showed that all constructs met the required validity and reliability criteria, and the model explained 38.7% of the variance in patient satisfaction (R² = 0.387). Health literacy demonstrated a positive but nonsignificant effect, while participation in decision-making and self-efficacy exhibited positive and significant influences. Pelayanan kesehatan yang berorientasi pada patient-centered care menekankan pentingnya literasi kesehatan dan self-efficacy pasien agar berperan aktif dalam setiap proses pengambilan keputusan medis yang berkaitan dengan kondisi kesehatannya. Pendekatan ini menempatkan pasien sebagai mitra bagi tenaga kesehatan, bukan sekadar penerima layanan. Meskipun demikian, pada rumah sakit pemerintah seperti RS Bhayangkara Semarang, tingkat kepuasan pasien masih beragam, terutama terkait aspek komunikasi antara pasien dan tenaga kesehatan, keterlibatan pasien dalam proses penentuan tindakan medis, serta pemahaman pasien terhadap informasi medis yang disampaikan. Penelitian ini dilakukan untuk menilai sejauh mana literasi kesehatan, partisipasi dalam pengambilan keputusan, dan self-efficacy berpengaruh terhadap kepuasan pasien rawat jalan. Penelitian ini menerapkan pendekatan kuantitatif dengan rancangan potong lintang (cross-sectional) dan melibatkan 220 pasien rawat jalan yang diperoleh melalui metode purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert yang telah dimodifikasi dari instrumen HLQ, PAM-13, GSE, dan PSQ. Proses analisis dilakukan menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) melalui aplikasi SmartPLS 4 untuk menilai validitas, reliabilitas, serta keterkaitan antarvariabel dalam model. Temuan penelitian memperlihatkan bahwa seluruh konstruk memenuhi kriteria validitas dan reliabilitas, dengan model penelitian mampu menjelaskan 38,7% variasi kepuasan pasien (R² = 0,387). Literasi kesehatan berpengaruh positif tetapi tidak signifikan terhadap kepuasan (β = 0,084), sedangkan partisipasi keputusan (β = 0,412) dan self-efficacy (β = 0,240) memberikan dampak positif yang bermakna. Temuan studi ini menegaskan prinsip patient-centered care dan teori self-determination, bahwa kepuasan pasien tidak ditentukan oleh mutu layanan medis, tetapi dipengaruhi oleh tingkat keterlibatan pasien dalam perawatan, kemampuan literasi kesehatannya, serta self-efficacy yang dimilikinya.